From the un-mixing to the re-mixing of peoples: Understanding the quest to “reverse ethnic cleansing” in Bosnia - Brubaker, R; Rebecca Brubaker (2014)
This dissertation focuses on international actors' response to the ethnic cleansing perpetrated during the 1992 – 1995 Bosnian War. The work illuminates the multilateral attempt to reverse one of the outcomes of ethnic cleansing following the war, through the return of displaced people. The policy emphasis on "re-mixing" people, interpreted through a strategy of minority returns, and supported and coordinated on an international scale, was unprecedented. This dissertation asks: why did powerful states and international organizations pursue a re-mixing policy as a response to ethnic cleansing in Bosnia? At first glance, the choice seems counterintuitive. The policy was expensive. Post-1989, the West no longer needed "to keep Yugoslavia afloat." Furthermore, reversal required a degree and duration of international involvement that, at the time, was thought to be politically, militarily, and financially impossible. There are two existing explanations for this surprising phenomenon: international moralism and norm evolutionism. International moralists posit that international actors were moved to re-mix Bosnians out of a sense of guilt. Norm evolutionists argue that international norms governing appropriate responses to ethnic cleansing have shifted during the twentieth century towards support for re-mixing. In contrast to these two dominant views, this dissertation argues that the re-mixing policy initially emerged as a practical fix to a series of pressing, context-specific political challenges. State policymakers justified the re-mixing policy, however, on normative grounds. Though not the original incentive for action, international organizations on the ground then adopted the policy, empowered by states' normative justifications and thereby transformed the political rhetoric into concrete action. This dissertation corrects a common assumption that the origins and motivations behind the re-mixing policy were normative in nature, it contributes to a better understanding of how normative discourses emerge, mature, and transform into policy and it offers policy recommendations based on lessons learnt from this important and seemingly contradictory case.